Evaluation of conjunctival flora in congenital ptosis - Balbaba, Mehmet; Ulas, Fatih; Canleblebici, Mehmet; Guven, Ozan; Toraman, Zulal Asci; Yildirim, Hakan; Erdag, Murat (Ijo Press, 2025)
AIM: To assess and compare the conjunctival bacterial flora in patients with congenital ptosis (CP) to that of healthy individuals. METHODS: The study included 38 patients with CP and 42 healthy control subjects. Conjunctival cultures were collected using a cotton-tipped swab applied to the inferior conjunctival fornix. The samples were inoculated into blood agar, eosin methylene blue agar, chocolate agar for bacteria, and Sabouraud dextrose agar medium for fungi. RESULTS: The culture positivity rate was 68.4% in CP and 47.6% in the control group (P<0.001). Additionally, there was a significant difference in culture positivity between the eyes of patients with unilateral ptosis (P=0.039). In the CP group, the most common found microorganism was Staphylococcus epidermidis at 23.67%, followed by Haemophilus species at 21.04%, and Corynebacterium species at 15.78%. In the control group, Staphylococcus epidermidis and Corynebacterium species were both the most commonly isolated microorganisms, each accounting for 19.04%. More than one species of bacteria was grown in the cultures of 36.84% and 23.80% of the CP and control subjects, respectively. Gram-negative bacteria were more common in CP than in control subjects (P=0.031). CONCLUSION: Culture positivity is significantly higher in the ptotic eyes of CP. Potentially pathogenic microorganisms are more frequently isolated from the CP group compared with the healthy control group.
Keywords: congenital ptosis; conjunctival flora; bacteria